Gamification of E-Participation: A Literature Review - Lobna Hassan; Juho Hamari (United States, 2022)
Gamification is one of the most commonly employed approaches for motivating individuals to participate in several types of activities. One of its largest application areas has been e-participation (i.e. citizen engagement in policy-making). Even though the required ICT infrastructure to facilitate e-participation mostly exists today, the focus of the problem has shifted towards humans; citizens are not motivated enough to participate. Gamification is a potential approach to increase motivation towards eparticipation. However, currently there is a dearth in our understanding of how gamification is being applied and researched as well as what kinds of result there exist from gamification. The aim of this paper is to synthesize research and findings on gamified eparticipation, providing directions for future research in this area.
Proceedings of the 52nd International Conference on System Sciences